2021
DOI: 10.1186/s13102-021-00373-2
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of intermittent pneumatic compression and negative pressure therapy on muscle function, soreness and serum indices of muscle damage: a randomized controlled trial

Abstract: Background The study aimed to assess whether intermittent pneumatic compression (IPC) and intermittent negative pressure (INP) would attenuate the muscle damaging effects of eccentric exercise. Methods Forty-five healthy males were recruited. Immediately post, 24 and 48 h post eccentric exercise consisting of 100 drop jumps, volunteers randomly received 30-min sessions of intermittent pneumatic compression (IPC, n = 15) or intermittent negative pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
5
0
4
Order By: Relevance
“…6,11, 12 The summary of the studies can be seen in Table 1. Wiecha (2021) found that no glaring distinction in recovery between groups after exercise-induced muscle damage in Intermittent Negative Pressure (INP) or IPC versus placebo in any measurement indicators of biochemical or functional measurement (strength, pain, or joint mobility). However, there was a significant time effect in the VAS score of muscle soreness, reduction in muscle strength, and range of active knee flexion.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…6,11, 12 The summary of the studies can be seen in Table 1. Wiecha (2021) found that no glaring distinction in recovery between groups after exercise-induced muscle damage in Intermittent Negative Pressure (INP) or IPC versus placebo in any measurement indicators of biochemical or functional measurement (strength, pain, or joint mobility). However, there was a significant time effect in the VAS score of muscle soreness, reduction in muscle strength, and range of active knee flexion.…”
Section: Resultsmentioning
confidence: 98%
“…Peak Lactate Dehydrogenase (LDH) levels were observed 1 hour after exercise, with a significant rise as soon as 1 hour after training. 11 Draper (2020) compared the order effect of the first run against the second run, the results shown that no significant difference in any variables except for one of the pain ratings. as comparing the pain experienced immediately following the first run against the second run, runners shows that they feel more pain in the second run than the first run.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies used a one-time protocol to assess the time of post-workout regeneration. The most reliable method would be to use it multiple times under different conditions to maximize results accuracy [33].…”
Section: Discussionmentioning
confidence: 99%
“…Але ППК не впливає на рівень С-реактивного протеїна [9] і не прискорює ресинтез глікогену [10]. Вплив ППК на лактат плазми остаточно не встановлений, є як спостереження відсутності такого впливу [11,12], так і спостереження позитивних ефектів [13].…”
unclassified
“…За використаними протоколами лікування ППК не мала позитивного впливу на м'язову силу і відновлення фізичної працеспроможності [10][11][12][13][14].…”
unclassified